Narrative structures in the poem of the traveling fly For Dr. Sheikh Ahmed Al-Waeli (Journal of the College of Basic Education, 2022)
This research studies the structure of the narrative in a poem (fly passenger), Dr. Sheikh Ahmed al-Waeli, a poem by the fly rode on the shoulder of the poet on his way to enter the plane in one of the airports when traveling, and it was more pushed back again until it got him at the airport so he said this poem. The paper deals with narrative elements author of this poem: the narrative of events, the characters, the environment, and dialogue, and the idea. Researcher and tries to throw light on the symbolic construction in this poem is symbolic of the characters, and the symbolic title of the poem, and its language and style